Anethum graveolens: An Indian traditional medicinal herb and spice - Jana, S.; Shekhawat, G. S. (Pharmacognosy Reviews)
Anethum graveolens L. (dill) has been used in ayurvedic medicines since ancient times and it is a popular herb widely used as a spice and also yields essential oil. It is an aromatic and annual herb of apiaceae family. The Ayurvedic uses of dill seeds are carminative, stomachic and diuretic. There are various volatile components of dill seeds and herb; carvone being the predominant odorant of dill seed and α-phellandrene, limonene, dill ether, myristicin are the most important odorants of dill herb. Other compounds isolated from seeds are coumarins, flavonoids, phenolic acids and steroids. The main purpose of this review is to understand the significance of Anethum graveolens in ayurvedic medicines and non-medicinal purposes and emphasis can also be given to the enhancement of secondary metabolites of this medicinal plant.
Keywords: Anethum graveolens; ayurvedic uses; carvone; limonene; monoterpenes; review